85.4k views
5 votes
Solve by substitution:
-5x + y = -2
-3x + 6y = -12

please explain

User Julx
by
4.9k points

1 Answer

2 votes

First we pick the equation. Let's say we pick first one. From it we express y.


-5x+y=-2\Longrightarrow y=-2+5x

Then we use this y and plug it in instead of y in the second equation.


-3x+6(-2+5x)=-12

Now just solve for x.


</p><p>-3x-12+30x=-12 \\</p><p>-3x=-30x \\</p><p>\underline{x=10}</p><p>

We plug this x in the first equation.


-5\cdot10+y=-2

And solve for y.


</p><p>-50+y=-2 \\</p><p>\underline{y=48}</p><p>

So the solution to the equation is geometrically a point P which lies on the intersection of the two lines.


\boxed{P(10,48)}

Hope this helps.

r3t40

User SureshAtt
by
5.1k points